A location’s potential for cultural and creative offer and its contribution to tourism: an evaluation method - Corá, Jacqueline Maria; de Alcântara Bittencourt César, Pedro (RITUR - Revista Iberoamericana de Turismo, 2024)
In a contemporary context in which more than half of the population is urban, cities are taking center stage and are challenged to (re)discover new resources in order to meet the different demands of society. In this context, the cultural and creative offer comes to be understood as a strategic resource in the economic and, through the cultural and creative industries and creative tourism, generates positive externalities that promote local sustainable development. This highlights the need to identify and value practices that use culture and creativity to add value to the city and contribute to its sustainability. Based on this understanding, the aim of this study is to develop a method for understanding a location’s potential for offering cultural and creative activities (CCAs), including goods and services, with an emphasis on creative tourism. To this end, the study is based on the Weberian comprehensive method, which proposes the construction of an Ideal Type model bringing together all the particularities found in phenomena of the same nature, thus obtaining an abstract and utopian model, whose main objective is to establish a confrontation with the reality observed empirically. In this way, the qualitative, exploratory type of research adopted a theoretical review as its methodological procedure, followed by a content analysis of 16 applied studies, which enabled the key aspects necessary for the construction of the instrument to be listed. The result was a Practical-Theoretical Model (PTM) consisting of six Dimensions (Human, Economic, Social, Cultural, Governance and Instrumental); 16 categories of analysis (Talent, Production, Education, Identity and Belonging, Culture, History and Memory, Resilience, Relational, Collective Intelligence and Public Management, Environment, Technologies, Infrastructure and Resources, Digital Economy, Employment and Income and Development), based on which the indicators and variables for evaluating the locality in terms of CCAs and their relationship with tourism were listed.